Malignant Catatonia Mimicking Pheochromocytoma - Sophia Wong; Barbara Hughes; Morris Pudek; Dailin Li (Case Reports in Endocrinology)
Malignant catatonia is an unusual and highly fatal neuropsychiatric condition which can present with clinical and biochemical manifestations similar to those of pheochromocytoma. Differentiating between the two diseases is essential as management options greatly diverge. We describe a case of malignant catatonia in a 20-year-old male who presented with concurrent psychotic symptoms and autonomic instability, with markedly increased 24-hour urinary levels of norepinephrine at 1752 nmol/day (normal, 89–470 nmol/day), epinephrine at 1045 nmol/day (normal, <160 nmol/day), and dopamine at 7.9 μmol/day (normal, 0.4–3.3 μmol/day). The patient was treated with multiple sessions of electroconvulsive therapy, which led to complete clinical resolution. Repeat urine collections within weeks of this presenting event revealed normalization or near normalization of his catecholamine and metanephrine levels. Malignant catatonia should be considered in the differential diagnosis of the hypercatecholamine state, particularly in a patient who also exhibits concurrent catatonic features.